2011
DOI: 10.3904/kjim.2011.26.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Guidelines for Empirical Therapy of Neutropenic Fever in Korea

Abstract: Neutrophils play an important role in immunological function. Neutropenic patients are vulnerable to infection, and except fever is present, inflammatory reactions are scarce in many cases. Additionally, because infections can worsen rapidly, early evaluation and treatments are especially important in febrile neutropenic patients. In cases in which febrile neutropenia is anticipated due to anticancer chemotherapy, antibiotic prophylaxis can be used, based on the risk of infection. Antifungal prophylaxis may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 202 publications
(254 reference statements)
0
71
0
Order By: Relevance
“…In fact, hematopoietic stem cell transplantation is a curative therapy to hematological malignancy. Hematological malignancy patients and hematopoietic stem cell transplant recipients are high-risk patients who are prone to getting causative agent infection, especially, increasing the risk from latent to active TB (Lee et al, 2011). Nearly one third of the world's population is infected with mycobacterium tuberculosis (Dolin et al, 1994), and the rate continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, hematopoietic stem cell transplantation is a curative therapy to hematological malignancy. Hematological malignancy patients and hematopoietic stem cell transplant recipients are high-risk patients who are prone to getting causative agent infection, especially, increasing the risk from latent to active TB (Lee et al, 2011). Nearly one third of the world's population is infected with mycobacterium tuberculosis (Dolin et al, 1994), and the rate continues to increase.…”
Section: Introductionmentioning
confidence: 99%
“…In two other studies conducted in Malaysia and Pakistan the same trend was observed (2,11). Dong-Gun Lee et al (12) mentioned that as a general characteristic of Asia-Pacific region, Gramnegative microorganisms were the major pathogens of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of mucormycosis, in particular, has been increasing along with the increasing use of antifungal agents with anti-Aspergillus activity, such as voriconazole [2,3] and it is the third most common fungal infection after candidiasis and aspergillosis [4]. In addition, because voriconazole has no activity in mucormycosis but results in better survival of patients with invasive pulmonary aspergillosis (IPA) than amphotericin B [5,6], distinguishing between IPA and pulmonary mucormycosis (PM) is important clinically. Although definite diagnoses can be made by combining histomorphologic diagnosis with fungal culture results, cultures are often negative, especially for mucormycosis [1].…”
mentioning
confidence: 99%